(untitled) (Research, Society and Development, 2020)
Objective: to know the care practices of nurses when caring for pregnant women and the cultural influence in this process. Methodology: it was an ethno-nursing, which was carried out with five nurses working in low-risk prenatal care, from primary health care in a city in Rio Grande do Sul. Data collection was developed from March to August of 2013, with participant observation and semi-structured interview. Results: the results of this study were analyzed according to Leininger and revealed the themes: “Low risk prenatal nursing care permeated by interaction” and “Nursing care permeated by culture”. Conclusion: it was concluded that nursing care in low-risk prenatal care is involved in guidelines and information from scientific knowledge. It was noteworthy that cultural aspects were present in nursing actions, underpinning the alliance between scientific and popular knowledge, allowing the active participation of nurses in the care of pregnant women.